(untitled) (Eureka Journal of Humanities and Social Research, 2026)
This article examines exchange rate pass-through, import prices, and inflation stabilization in Uzbekistan during 2018–2025. After the 2017 currency liberalization reforms, Uzbekistan experienced significant exchange rate fluctuations that increased import prices and created inflationary pressure. Since the economy depends heavily on imported goods such as food, fuel, machinery, and medicines, exchange rate volatility became an important factor affecting domestic price stability.